A New Evaluation Method for the Fracability of a Shale Reservoir Based on the Structural Properties. (4th December 2019) - Sui, Haoyue; Gao, Wei; Hu, Ruilin
Abstract : The fracability of shale reservoirs is one of the key indicators used for evaluating whether or not the shale can be used as a "sweet spot zone." It has been determined that the structural properties of rock have important influences on the evaluation of the fracability of reservoirs. In the current study, five rock quality designation (RQD) calculation methods were compared and analyzed for the purpose of selecting an RQDI for characterizing rock structures. Focused on the lack of structural factors included in the previous fracability evaluation methods, a new model for fracability evaluation based on the combination of the brittleness index, structural index, and fracture toughness was constructed using a linear elastic fracture theory. The model showed that good fracability not only included higher brittleness but also required less energy to produce cracks. Meanwhile, good fracability also required more discontinuous structural planes. In the current study, a formation with a higher fracability index was considered to be a fractureable interval and a formation with a lower fracability index was a fracture barrier. Finally, the reservoir fracability index was modeled using the Xike 2 well in the north of Guizhou Province as a case study. Subsequently, a fracability logging evaluation method based on the fracability index model was determined, which will potentially provide a new technical tool for future fracturing optimization processes.